Huntley Complement while Determining Area of Rational Pressurized Ventilation Usage - Ya. A. Gusentsova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An optimum utilization criterion for pressurized  ventilation and air heating systems of public and office buildings has been obtained on the basis of generalized mathematical model of thermal and aerodynamic characteristics of air heating and ventilation systems.